The use of remote video directly observed therapy to improve both inhaler technique and adherence to asthma medications - Paddy McCrossan; Paddy McCrossan; Dara O'Donoghue; Dara O'Donoghue; James Charles McElnay; Michael D. Shields; Michael D. Shields (Frontiers Media S.A., 2022)
Incorrect inhaler technique and non-adherence to inhaled preventer therapy often is the cause of poorly controlled asthma. Detecting and correcting non-adherence in asthma therapy has proven difficult. In addition, while patients may be able to demonstrate correct inhaler technique at the clinic recent evidence suggests that critical errors in inhaler technique occur in the home setting. Remote video directly observed therapy (vDOT) has recently been described as a potentially useful tool for addressing non-adherence while also allowing timely correction of inhaler technique errors. In this mini-review we describe the use of vDOT in asthma management.